Desarrollo de una propuesta de mejora para el proceso de producción de sulfato de magnesio (mgso4) usado como fertilizante en Hebesta S.A.S. (2018)
In the following degree work, an improvement proposal for the production of magnesium sulfate heptahydrate (MgSO4 * 7H2O) is described in the company Hebesta S.A.S.. to be used as fertilizer because it shows deficient in the dosage, the use in the excess of raw materials and in the final product, because the procedure is performed empirically and manually. A total diagnosis of the production process was made, the quality of the raw material and the final product was evaluated, as well as the evaluation of the main properties of a fertilizer, such as solubility, granulometry, density and ph, the state was evaluated current equipment, the tasks performed by each operation in each of the stages that make up the production process (reaction, decantation, crystallization, centrifugation and packaging) and also the development in each of the characteristics, then identified the major faults from a Pareto diagram.